2015
DOI: 10.1093/infdis/jiv499
|View full text |Cite
|
Sign up to set email alerts
|

Middle East Respiratory Syndrome Coronavirus Causes Multiple Organ Damage and Lethal Disease in Mice Transgenic for Human Dipeptidyl Peptidase 4

Abstract: Middle East respiratory syndrome coronavirus (MERS-CoV) causes life-threatening disease. Dipeptidyl peptidase 4 (DPP4) is the receptor for cell binding and entry. There is a need for small-animal models of MERS, but mice are not susceptible to MERS because murine dpp4 does not serve as a receptor. We developed transgenic mice expressing human DPP4 (hDPP4) under the control of the surfactant protein C promoter or cytokeratin 18 promoter that are susceptible to infection with MERS-CoV. Notably, mice expressing h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

12
458
0
21

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 425 publications
(491 citation statements)
references
References 47 publications
12
458
0
21
Order By: Relevance
“…Generation of transgenic mice expressing a virus receptor is a common strategy to make mice permissive to infection. Several groups in addition to ours developed mice with transgenic expression of hDPP4 using different promoters [25][26][27][28]. The disease severity following MERS-CoV infection in transgenic mice correlated with the cellular distribution and expression level of hDPP4.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…Generation of transgenic mice expressing a virus receptor is a common strategy to make mice permissive to infection. Several groups in addition to ours developed mice with transgenic expression of hDPP4 using different promoters [25][26][27][28]. The disease severity following MERS-CoV infection in transgenic mice correlated with the cellular distribution and expression level of hDPP4.…”
Section: Introductionmentioning
confidence: 95%
“…The disease severity following MERS-CoV infection in transgenic mice correlated with the cellular distribution and expression level of hDPP4. In transgenic mice expressing hDPP4 driven by the cytokeratin 18 promoter [26] or a ubiquitous promoter [25,27,28], MERS-CoV replicates and causes respiratory disease and mortality. However, the lethality was found to be secondary to overwhelming central nervous system (CNS) disease or multiorgan damage.…”
Section: Introductionmentioning
confidence: 99%
“…The other type of MERS-CoV-susceptible mice available to date includes knockin strains in which 3 or 13 exons of mouse DPP4 have been replaced with the homologous sequences from hDPP4 Li et al, 2016;Pascal et al, 2015). A major difference to the Tg mice described earlier is that the mouse-adapted MERS-CoV only produced disease in knockin mice after the virus has been passed 30 times in the knockin mouse (K. Li, P. McCray, and S. Perlman, 2016, personal communication), whereas the LD50 of MERS-CoV in these mice was around 10 4 pfu/ mouse.…”
Section: Animal Models For Cov Vaccine and Antivirals Studiesmentioning
confidence: 99%
“…Finally, a recent study has demonstrated that mice transgenic for hDPP4 under the epithelial-cell-specific promoters also support widespread MERS-CoV infection resulting in significant damage in the lungs and brain of infected mice (26). Although this model is improved relative to previously reported mouse models by limiting hDPP4 expression to epithelial cells, this is not coincident with the levels of expression and cell types in which endogenous mDPP4 is found.…”
mentioning
confidence: 94%
“…All three models of MERS-CoV infection in mice (22,25,26) have robust replication of MERS-CoV and, as such, have utility as a vehicle for testing of novel therapeutics or vaccines that inhibit MERS-CoV replication (25,26). However, they provide limited information about the natural pathogenesis of MERS-CoV infection in vivo (25).…”
mentioning
confidence: 99%